Localized response performance of the decoupled Q -V network - Ilic-Spong, M.; Thorp, J.; Spong, M. (IEEE transactions on circuits and systems, 1986)
In this paper the assumption of a localized voltage response due to reactive power disturbances is analyzed. Conditions on transmission line parameters, given its normal operating point, are stated which explicitly define directions of voltage changes so that the line is subject to the localized voltage response. We show that it is not possible to give an exclusive answer to the question of the localized response (tier-wise) in the decoupled Q - V network. The answer is network and operating point dependent. The operating regions in which this property is satisfied even under large changes in reactive power injections are derived on the SE graph based decoupled Q- V network. We first define a no-gain operating mode of this network and then claim that the power no-gain operating mode always implies a localized voltage response. These results cannot be used to demonstrate a voltage gain. We develop algebraic type statements to show that a system may have response which is system wide. More definite answers on the localized response are established for the echelon structure of a given network.